Implikasi Putusan Mahkamah Konstitusi Nomor 101/Puu-VII/2009 terhadap Pelaksanaan Profesi Advokat di Daerah Istimewa Yogyakarta - Pusat Kajian Hukum Konstitusi FH UJB (The Constitutional Court of the Republic of Indonesia, 2016)
The research showed that: (1) the response of the lawyers who have not sworn by the high court of Yogyakarta is that the Constitutional Court decision No. 101/PUU-VII/2009 expected to solve the problems KAI advocates, however, the constitutional court decision has not been carried out by competent parties.Recently, the KAI Advocate cannot administering the advocate’s oath in the open court of high court of Yogyakarta (2) the decision of the constitutional court no. No. 101/PUU-VII/2009 was not provide any implications for the organization advocates and implementation of professional lawyers in Yogyakarta, (3) the attitude of judges towards lawyers who are not appointed by the high court in the court’s proceedings, there was no difference attitude compared to the prior existence of the constitutional court decision.Practically, judges allow lawyers who have not sworn to proceed and become a legal counsel at the hearing, the proceedings if the advocate or be accompanied by legal counsel or stuck in a legal advocate and has been sworn in, (4) there was not any action of high court of Yogyakarta as the implementation of the constitutional court decision No. 101/PUU- VII/2009. This is due to the high court of Yogyakarta was not as a party in the constitutional court decision, thus they were not implement the decision.